Heterogeneous polyolefin composite particle asphalt modifier and preparation method thereof

By copolymerizing the recycled EVA plastic particles, waste tire rubber particles, crosslinking agents and additives in the twin-screw extruder and adding high-strength fiber capsules to form a heterogeneous polyolefin composite particle asphalt modifier, the problems of structural instability and phase separation during physical blending are solved, and the coordinated enhancement of high and low temperature performance and the recycling and regeneration of waste materials are achieved.

CN119613837APending Publication Date: 2025-03-14KUNMING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411879223.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The physical blending process of waste plastic and waste rubber cannot form a crosslinked structure, resulting in structural instability and phase separation of asphalt modifiers, affecting their high and low temperature performance.

Method used

The formation of a physical or chemical crosslinking structure is achieved by copolymerizing the recycled EVA plastic particles, waste tire rubber particles, crosslinking agents and additives in a twin-screw extruder and adding high-strength fiber capsules.

Benefits of technology

This method not only improves the coordinated enhancement of high and low temperature performance of asphalt modifiers, but also improves its structural stability and phase separation problems, realizes the recycling and regeneration of waste materials, and reduces environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005197763600000081
    Figure BDA0005197763600000081
Patent Text Reader

Abstract

The invention discloses a heterogeneous polyolefin composite particle asphalt modifier and a preparation method thereof, and belongs to the field of asphalt modifier preparation. The heterogeneous polyolefin composite particle asphalt modifier is prepared from the following components in parts by weight: 10 to 20 parts of recycled EVA (Ethylene Vinyl Acetate) plastic particles, 10 to 20 parts of recycled ABS (Acrylonitrile Butadiene Styrene) plastic particles, 60 to 80 parts of waste tire rubber particles, 2 to 3.5 parts of high-strength fiber capsules, 0.5 to 1.5 parts of cross-linking agent and 0.1 to 0.5 part of auxiliary agent. The waste regenerated polyolefin material is melted and copolymerized to form the composite particles, so that the composite particles have the characteristics of high rigidity of plastic and high toughness of rubber at the same time. When the heterogeneous polyolefin composite particles are used for modifying asphalt, not only can the excellent high-low temperature rheological property of the modified asphalt be realized, but also the crosslinking effect of regenerated rubber and regenerated plastic parts is promoted, and the storage stability of the modified asphalt is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a multiphase polyolefin composite particle asphalt modifier and a preparation method thereof, belonging to the field of asphalt modifier preparation. Background Art

[0002] Petroleum asphalt is an important raw material for asphalt pavement. Petroleum asphalt is a low polymer material, which is prone to rutting deformation under high temperature in summer and heavy vehicle load, and brittle cracking in low temperature in winter. At present, adding high molecular polymer modifiers to the asphalt matrix is ​​a common method to improve its high temperature resistance to rutting, low temperature resistance to cracking and long-term fatigue resistance. Compared with the high-cost SBS modifier, the use of waste plastics or rubber as asphalt modifiers is not only conducive to enhancing the service performance of the base asphalt, but also can promote the resource application of solid waste, and has become a research hotspot in recent years.

[0003] Waste plastic particles have the characteristic of high hardness. Although they can greatly improve the high-temperature anti-rutting performance of the base asphalt, they damage the low-temperature anti-cracking performance. Waste rubber products have the characteristic of good ductility, which can improve the low-temperature anti-cracking performance of the base asphalt, but the enhancement effect on high-temperature performance is limited. Based on the mechanical properties of waste plastics and waste rubber, blending the two to prepare asphalt modifiers is of great significance to achieve synergistic enhancement of the high and low temperature performance of the base asphalt. However, the physical blending process of waste plastics and waste rubber cannot form a cross-linked structure, which is prone to structural instability and phase separation problems.

[0004] Waste plastic and waste rubber are melt-copolymerized to form a copolymer with a physical or chemical cross-linking structure, which has the characteristics of high hardness of plastic and strong toughness of rubber. On this basis, the use of waste plastic-rubber copolymers to prepare modified asphalt can achieve synergistic enhancement of the high and low temperature performance of asphalt materials, and better improve the structural instability and phase separation problems of plastic modified asphalt. Summary of the invention

[0005] In order to solve the problem that the physical blending process of waste plastics and waste rubber cannot form a cross-linked structure, which easily causes structural instability and phase separation, one of the purposes of the present invention is to provide a multiphase polyolefin composite particle asphalt modifier, which comprises the following components in parts by weight: 10-20 parts of recycled EVA plastic particles (ethylene-vinyl acetate copolymer plastic particles), 10-20 parts of recycled ABS plastic particles (terpolymer plastic particles of three monomers: acrylonitrile, butadiene, and styrene), 60-80 parts of waste tire rubber particles, 2-3.5 parts of high-strength fiber capsules, 0.5-1.5 parts of cross-linking agent and 0.1-0.5 parts of auxiliary agent.

[0006] Preferably, the preparation method of the high-strength fiber capsule is as follows:

[0007] (1) fully mixing an isocyanate resin and ethyl acetate to obtain an oil phase, adding the oil phase to an aqueous phase made of soybean polysaccharide and deionized water, and stirring under heating to obtain a capsule suspension for later use;

[0008] (2) ordinary fiber is mixed with the capsule suspension prepared in step (1), stirred and ultrasonically treated, filtered, washed with deionized water to a pH of 6.8-7.2, and dried to obtain high-strength fiber capsules.

[0009] Preferably, in step (1), the weight ratio of isocyanate resin to ethyl acetate is: (2-3):(1.5-4.5); the solid-liquid ratio of soybean polysaccharide to deionized water is (2.5-4.5):(30-50), in units of g:ml.

[0010] Preferably, in step (1), the volume ratio of the oil phase to the water phase is (1-2):(1.5-2.5).

[0011] Preferably, the heating temperature in step (1) is 50-70°C.

[0012] Preferably, in step (2), the solid-liquid ratio of common fiber to capsule suspension is 2:(50-60), expressed in g:ml; the common fiber is one of poly(p-phenylene benzobisoxazole) fiber, carbon fiber, and polyimide fiber.

[0013] Preferably, the crosslinking agent is formed by mixing ethylene-octene copolymer and functional aminosiloxane in a weight ratio of (2-3):(1.5-3.5), and the functional aminosiloxane is one of 3-aminopropyldimethoxymethylsilane and self-ureapropyltriethoxysilane.

[0014] Preferably, the auxiliary agent is composed of an oxidant, a softener and a promoter in a weight ratio of (1-2): (2-3): (0.5-1); the antioxidant is one or two of 2,6-di-tert-butyl-p-cresol and 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane mixed in any proportion; the softener is one or two of dioctyl terephthalate, dioctyl phthalate and dibutyl phthalate mixed in any proportion; the promoter is one or two of promoter ZDC (zinc diethyldithiocarbamate) and promoter CZ (N-cyclohexyl-2-benzothiazolesulfonamide) mixed in any proportion.

[0015] Preferably, the waste tire rubber is 40-100 mesh waste tire rubber particles.

[0016] Another object of the present invention is to provide a method for preparing a multiphase polyolefin composite particle asphalt modifier, comprising adding recycled EVA plastic particles, waste tire rubber powder particles, a crosslinking agent and an auxiliary agent into a twin-screw extruder, mixing for 10-20 minutes at a temperature of 50-70°C and a rotation speed of 100-200 rpm, adding recycled ABS plastic particles and high-strength fiber capsules in proportion after uniform mixing, continuing to mix for 15-25 minutes at a temperature of 50-70°C and a rotation speed of 100-200 rpm, and then extruding and granulating to obtain a multiphase polyolefin composite particle asphalt modifier.

[0017] Beneficial effects of the present invention

[0018] (1) The present invention realizes the uniform dispersion of fiber materials in the system of recycled EVA, ABS plastic particles and waste tire rubber powder through high-strength fiber capsules. At the same time, organic matter grafted on the surface of high-strength fiber capsules can promote the interfacial cross-linking between them and EVA, ABS and rubber powder, thereby enhancing the structural stability of the system.

[0019] (2) In the present invention, recycled EVA and ABS plastic particles and waste tire rubber powder particles are copolymerized to form multiphase polyolefin composite particles, so that they have the dual advantages of high hardness plastic and strong toughness rubber.

[0020] (3) Using multiphase polyolefin composite particles as a matrix asphalt modifier is beneficial to improving high and low temperature service performance and storage stability.

[0021] (4) The main synthetic raw materials in the invention are derived from waste polymer materials, which not only can obtain modified asphalt with better performance, but also achieve the recycling rate of waste materials, effectively reducing environmental pollution. DETAILED DESCRIPTION

[0022] The technical solution of the present invention is further described below by specific implementation methods. However, the following embodiments are only simple examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.

[0023] Example 1

[0024] A preparation method of a multiphase polyolefin composite particle asphalt modifier comprises the following steps:

[0025] (1) isocyanate resin and ethyl acetate are mixed in a weight ratio of 2:3 to obtain an oil phase, and soybean polysaccharide and deionized water are mixed in a solid-liquid ratio of 3:40 (g:ml) to obtain an aqueous phase; the oil phase is slowly added to the aqueous phase at 50°C, the volume ratio of the oil phase to the aqueous phase is 1:2.5, and the capsule suspension is obtained after stirring for 1 hour.

[0026] (2) 2 g of polyimide fiber was added to 50 ml of capsule suspension, stirred and ultrasonically treated, filtered, and repeatedly washed with deionized water until the pH value was 7.0, and dried to obtain high-strength fiber capsules.

[0027] (3) Ethylene-octene copolymer and 3-aminopropyldimethoxymethylsilane are uniformly mixed in a weight ratio of 2:1.5 to obtain a crosslinking agent.

[0028] (4) 2,6-di-tert-butyl-p-cresol, dioctyl terephthalate and accelerator ZDC are uniformly mixed in a weight ratio of 1:2:1 to obtain an auxiliary agent.

[0029] (5) According to weight parts, 10 parts of recycled EVA plastic particles, 60 parts of waste tire rubber powder particles (40 mesh), 1 part of cross-linking agent and 0.3 parts of auxiliary agent were added into a twin-screw extruder, and mixed for 15 minutes at a temperature of 50°C and a rotation speed of 100 rpm. Subsequently, 15 parts of recycled ABS plastic particles and 3 parts of high-strength fiber capsules were added, and the mixture was further mixed for 15 minutes at a temperature of 50°C and a rotation speed of 100 rpm. After extrusion granulation, a multiphase polyolefin composite particle asphalt modifier was obtained.

[0030] Example 2

[0031] A preparation method of a multiphase polyolefin composite particle asphalt modifier comprises the following steps:

[0032] (1) isocyanate resin and ethyl acetate are mixed at a weight ratio of 2:4.5 to obtain an oil phase, and soybean polysaccharide and deionized water are mixed at a solid-liquid ratio of 2.5:30 (g:ml) to obtain an aqueous phase; the oil phase is slowly added to the aqueous phase at 70°C, the volume ratio of the oil phase to the aqueous phase is 1.5:2.5, and the capsule suspension is obtained after stirring for 1 hour.

[0033] (2) 2 g of carbon fiber was added to 60 ml of capsule suspension, stirred and ultrasonically treated, filtered, and repeatedly washed with deionized water until the pH value was 7.0, and dried to obtain high-strength fiber capsules.

[0034] (3) Ethylene-octene copolymer and ureapropyl triethoxysilane are uniformly mixed in a weight ratio of 3:3.5 to obtain a crosslinking agent.

[0035] (4) 1,1,3-tri(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, dioctyl phthalate and accelerator CZ were uniformly mixed in a weight ratio of 2:3:0.5 to obtain an auxiliary agent.

[0036] (5) According to weight parts, 20 parts of recycled EVA plastic particles, 80 parts of waste tire rubber powder particles (60 mesh), 0.5 parts of cross-linking agent and 0.1 parts of auxiliary agent were added into a twin-screw extruder, and mixed for 10 minutes at a temperature of 60°C and a rotation speed of 200 rpm. Subsequently, 20 parts of recycled ABS plastic particles and 3.5 parts of high-strength fiber capsules were added, and the mixture was mixed for another 10 minutes at a temperature of 60°C and a rotation speed of 200 rpm. After extrusion granulation, a multiphase polyolefin composite particle asphalt modifier was obtained.

[0037] Example 3

[0038] A preparation method of a multiphase polyolefin composite particle asphalt modifier comprises the following steps:

[0039] (1) isocyanate resin and ethyl acetate are mixed at a weight ratio of 3:1.5 to obtain an oil phase, and soybean polysaccharide and deionized water are mixed at a solid-liquid ratio of 4.5:50 (g:ml) to obtain an aqueous phase; the oil phase is slowly added to the aqueous phase at 50°C, the volume ratio of the oil phase to the aqueous phase is 2:2.5, and the capsule suspension is obtained after stirring for 3 hours.

[0040] (2) 2 g of poly(p-phenylene benzobisoxazole) fiber (PBO) was added to 60 ml of capsule suspension, stirred and ultrasonically treated, filtered, and repeatedly washed with deionized water until the pH value was 7.0, and dried to obtain high-strength fiber capsules.

[0041] (3) Ethylene-octene copolymer and 3-aminopropyldimethoxymethylsilane are uniformly mixed in a weight ratio of 2:1.5 to obtain a crosslinking agent.

[0042] (4) 2,6-di-tert-butyl-p-cresol, dibutyl phthalate and accelerator ZDC are uniformly mixed in a weight ratio of 1:2:1 to obtain an auxiliary agent.

[0043] (5) According to weight parts, 10 parts of recycled EVA plastic particles, 60 parts of waste tire rubber powder particles (80 mesh), 1.5 parts of cross-linking agent and 0.5 parts of auxiliary agent were added into a twin-screw extruder, and mixed for 15 minutes at a temperature of 70°C and a rotation speed of 100 rpm. Subsequently, 10 parts of recycled ABS plastic particles and 2 parts of high-strength fiber capsules were added, and the mixture was further mixed for 15 minutes at a temperature of 50°C and a rotation speed of 100 rpm. After extrusion granulation, a multiphase polyolefin composite particle asphalt modifier was obtained.

[0044] Comparative Example 1

[0045] For comparison, the difference between this comparative example and Example 1 is that the high-strength fiber capsule is replaced with ordinary polyimide fiber, and the specific preparation steps are as follows:

[0046] (1) Ethylene-octene copolymer and 3-aminopropyldimethoxymethylsilane are uniformly mixed in a weight ratio of 2:1.5 to obtain a crosslinking agent.

[0047] (2) 2,6-di-tert-butyl-p-cresol, dioctyl terephthalate and accelerator ZDC are uniformly mixed in a weight ratio of 1:2:1 to obtain an auxiliary agent.

[0048] (3) 10 g of recycled EVA plastic particles, 60 g of waste tire rubber powder particles (40 mesh), 1 g of a cross-linking agent and 0.3 g of an auxiliary agent were added into a twin-screw extruder and mixed for 15 min at a temperature of 50°C and a rotation speed of 100 rpm. Subsequently, 15 g of recycled ABS plastic particles and 3 g of polyimide fibers were added and mixed for another 15 min at a temperature of 50°C and a rotation speed of 100 rpm. After extrusion granulation, a multiphase polyolefin composite particle asphalt modifier was obtained.

[0049] Comparative Example 2

[0050] For comparison, the difference between this comparative example and Example 2 is that the high-strength fiber capsule is replaced with ordinary carbon fiber, and the specific preparation steps are as follows:

[0051] (1) Ethylene-octene copolymer and 3-aminopropyldimethoxymethylsilane are uniformly mixed in a weight ratio of 2:1.5 to obtain a crosslinking agent.

[0052] (2) 2,6-di-tert-butyl-p-cresol, dioctyl terephthalate and accelerator ZDC are uniformly mixed in a weight ratio of 1:2:1 to obtain an auxiliary agent.

[0053] (3) 10 g of recycled EVA plastic particles, 60 g of waste tire rubber powder particles (60 mesh), 1 g of a cross-linking agent and 0.3 g of an additive were added into a twin-screw extruder and mixed for 15 min at a temperature of 50°C and a rotation speed of 100 rpm. Subsequently, 15 g of recycled ABS plastic particles and 3 g of carbon fiber were added and mixed for another 15 min at a temperature of 50°C and a rotation speed of 100 rpm. After extrusion granulation, a multiphase polyolefin composite particle asphalt modifier was obtained.

[0054] Comparative Example 3

[0055] For comparison, the difference between this comparative example and Example 3 is that the high-strength fiber capsule is replaced with ordinary poly(p-phenylene benzobisoxazole) (PBO) fiber, and the specific preparation steps are as follows:

[0056] (1) Ethylene-octene copolymer and 3-aminopropyldimethoxymethylsilane are uniformly mixed in a weight ratio of 2:1.5 to obtain a crosslinking agent.

[0057] (2) 2,6-di-tert-butyl-p-cresol, dioctyl terephthalate and accelerator ZDC are uniformly mixed in a weight ratio of 1:2:1 to obtain an auxiliary agent.

[0058] (3) 10 g of recycled EVA plastic particles, 60 g of waste tire rubber powder particles (80 mesh), 1 g of a cross-linking agent and 0.3 g of an auxiliary agent were added into a twin-screw extruder and mixed for 15 min at a temperature of 50°C and a rotation speed of 100 rpm. Subsequently, 15 g of recycled ABS plastic particles and 3 g of poly(p-phenylene benzobisoxazole) fiber (PBO) were added and mixed for another 15 min at a temperature of 50°C and a rotation speed of 100 rpm. After extrusion granulation, a multiphase polyolefin composite particle asphalt modifier was obtained.

[0059] Comparative Example 4

[0060] As a comparison, the difference between this comparative example and Example 2 is that only 60-mesh waste tire rubber powder particles are used as the asphalt modifier.

[0061] Comparative Example 5

[0062] For comparison, the difference between this comparative example and the embodiment is step (5), and the other steps are exactly the same as in Example 1. In this comparative example, EVA plastic particles, 60g of waste tire rubber powder particles (40 mesh), 1g of cross-linking agent, 0.3g of auxiliary agent, 15g of recycled ABS plastic particles and 3g of high-strength fiber capsules are added into a twin-screw extruder at one time and mixed for 15 minutes at a temperature of 50°C and a rotation speed of 100rpm. After extrusion granulation, the asphalt modifier is obtained.

[0063] Comparative Example 6

[0064] For comparison, the difference between this comparative example and Example 1 is that the heating temperature in step (5) is lower than 50° C., the stirring speed is lower than 100 rpm, and the remaining steps are exactly the same as those in Example 1. The specific preparation steps are as follows:

[0065] (1) isocyanate resin and ethyl acetate are mixed in a weight ratio of 2:3 to obtain an oil phase, and soybean polysaccharide and deionized water are mixed in a solid-liquid ratio of 3:40 (g:ml) to obtain an aqueous phase; the oil phase is slowly added to the aqueous phase at 50°C, the volume ratio of the oil phase to the aqueous phase is 1:2.5, and the capsule suspension is obtained after stirring for 1 hour.

[0066] (2) 2 g of polyimide fiber was added to 50 ml of capsule suspension, stirred and ultrasonically treated, filtered, and repeatedly washed with deionized water until the pH value was 7.0, and dried to obtain high-strength fiber capsules.

[0067] (3) Ethylene-octene copolymer and 3-aminopropyldimethoxymethylsilane are uniformly mixed in a weight ratio of 2:1.5 to obtain a crosslinking agent.

[0068] (4) 2,6-di-tert-butyl-p-cresol, dioctyl terephthalate and accelerator ZDC are uniformly mixed in a weight ratio of 1:2:1 to obtain an auxiliary agent.

[0069] (5) 10 g of recycled EVA plastic particles, 60 g of waste tire rubber powder particles (40 mesh), 1 g of a cross-linking agent and 0.3 g of an auxiliary agent were added into a twin-screw extruder and mixed at a temperature of 40°C and a rotation speed of 100 rpm for 15 min. Subsequently, 15 g of recycled ABS plastic particles and 3 g of high-strength fiber capsules were added and mixed at a temperature of 50°C and a rotation speed of 90 rpm for another 15 min. After extrusion granulation, a multiphase polyolefin composite particle asphalt modifier was obtained.

[0070] Comparative Example 7

[0071] For comparison, the difference between this comparative example and Example 1 is that the heating temperature in step (5) is higher than 70° C. and the rotation speed is higher than 200 rpm. The remaining steps are exactly the same as those in Example 1. The specific preparation steps are as follows:

[0072] (1) isocyanate resin and ethyl acetate are mixed in a weight ratio of 2:3 to obtain an oil phase, and soybean polysaccharide and deionized water are mixed in a solid-liquid ratio of 3:40 (g:ml) to obtain an aqueous phase; the oil phase is slowly added to the aqueous phase at 50°C, the volume ratio of the oil phase to the aqueous phase is 1:2.5, and the capsule suspension is obtained after stirring for 1 hour.

[0073] (2) 2 g of polyimide fiber was added to 50 ml of capsule suspension, stirred and ultrasonically treated, filtered, and repeatedly washed with deionized water until the pH value was 7.0, and dried to obtain high-strength fiber capsules.

[0074] (3) Ethylene-octene copolymer and 3-aminopropyldimethoxymethylsilane are uniformly mixed in a weight ratio of 2:1.5 to obtain a crosslinking agent.

[0075] (4) 2,6-di-tert-butyl-p-cresol, dioctyl terephthalate and accelerator ZDC are uniformly mixed in a weight ratio of 1:2:1 to obtain an auxiliary agent.

[0076] (5) 10 g of recycled EVA plastic particles, 60 g of waste tire rubber powder particles (40 mesh), 1 g of a cross-linking agent and 0.3 g of an auxiliary agent were added into a twin-screw extruder and mixed for 15 min at a temperature of 40°C and a rotation speed of 110 rpm. Subsequently, 15 g of recycled ABS plastic particles and 3 g of high-strength fiber capsules were added and mixed for another 15 min at a temperature of 80°C and a rotation speed of 210 rpm. After extrusion granulation, a multiphase polyolefin composite particle asphalt modifier was obtained.

[0077] In order to illustrate the effect of the asphalt modifier prepared in the examples and comparative examples, the modifier prepared in the examples and comparative examples is further used to prepare modified asphalt, and the steps are as follows:

[0078] Calculated by weight, 12 parts of the asphalt modifiers prepared in the examples and comparative examples were added to 100 parts of No. 70 base asphalt, and sheared for 60 minutes using a high-speed shearing machine at a temperature of 175°C and a rotation speed of 2000 rpm, and then continued to develop at 65°C for 2 hours to obtain modified asphalt.

[0079] Table 1 shows the conventional performance indicators and phase separation indexes of the modified asphalts prepared in Examples 1-3 and Comparative Examples 1-7.

[0080] Table 1 Three major indicators and high temperature anti-rutting performance of the embodiments and comparative examples

[0081]

[0082] As can be seen from Table 1: The results of Example 1 and Comparative Examples 1-3 show that, compared with ordinary fibers, the use of high-strength fiber capsules is more conducive to improving the low-temperature ductility and storage stability of the multiphase polyolefin composite particle modified asphalt. The reason for choosing high-strength fiber capsules is that it is difficult for ordinary fibers to achieve chemical crosslinking between recycled EVA, ABS and rubber powder. The high-strength fiber is made into a capsule suspension system to achieve uniform dispersion of the fiber. At the same time, the isocyanate resin and ethyl acetate organic matter grafted on the fiber surface can be stably crosslinked with EVA, ABS and rubber powder, further enhancing the structural stability, ductility and crack resistance of the multiphase polyolefin composite particles, and achieving good storage stability and rheological properties of the asphalt modifier.

[0083] The results of Example 1 and Comparative Example 4 show that compared with a single polyolefin modifier, the multiphase polyolefin composite particle modified asphalt formed by melt copolymerization of recycled plastic and waste rubber powder exhibits better high temperature performance and storage stability.

[0084] The results of Example 1 and Comparative Example 5 show that when the EVA plastic particles and the waste tire rubber powder are first mixed and then the ABS plastic particles are added, the EVA plastic particles and the ABS plastic particles will not agglomerate, thereby ensuring good uniformity and structural stability of the copolymer.

[0085] The results of Example 1 and Comparative Examples 6 and 7 show that when the mixing temperature and rotation speed are too low, the recycled plastic particles have poor fluidity and are difficult to process, while when the mixing temperature or rotation speed is too high, it will cause material degradation and uneven blending.

[0086] It can be seen that the multiphase polyolefin composite particle modified asphalt under the present application scheme has better high and low temperature performance, while showing good storage stability and processing performance, and has high economic value.

Claims

1. A multiphase polyolefin composite particle asphalt modifier, characterized in that: The multiphase polyolefin composite particle asphalt modifier comprises the following components in parts by weight: 10-20 parts of recycled EVA plastic particles, 10-20 parts of recycled ABS plastic particles, 60-80 parts of waste tire rubber particles, 2-3.5 parts of high-strength fiber capsules, 0.5-1.5 parts of crosslinking agents and 0.1-0.5 parts of auxiliary agents.

2. The multiphase polyolefin composite particle asphalt modifier according to claim 1, characterized in that: The preparation method of the high-strength fiber capsule is as follows: (1) fully mixing isocyanate resin and ethyl acetate to obtain an oil phase, adding the oil phase to an aqueous phase made of soybean polysaccharide and deionized water, stirring under heating to obtain a capsule suspension, and setting aside; (2) ordinary fiber is mixed with the capsule suspension prepared in step (1), stirred and ultrasonically treated, filtered, washed with deionized water to a pH of 6.8-7.2, and dried to obtain high-strength fiber capsules.

3. The multiphase polyolefin composite particle asphalt modifier according to claim 2, characterized in that: In step (1), the weight ratio of isocyanate resin to ethyl acetate is: (2-3): (1.5-4.5); the solid-liquid ratio of soybean polysaccharide to deionized water is (2.5-4.5): (30-50), the unit is g:ml.

4. The multiphase polyolefin composite particle asphalt modifier according to claim 2, characterized in that: In step (1), the volume ratio of the oil phase to the water phase is (1-2):(1.5-2.5).

5. The multiphase polyolefin composite particle asphalt modifier according to claim 2, characterized in that: The heating temperature in step (1) is 50-70°C.

6. The multiphase polyolefin composite particle asphalt modifier according to claim 2, characterized in that: In step (2), the solid-liquid ratio of common fiber to capsule suspension is 2:(50-60), expressed in g:ml; the common fiber is one of poly(p-phenylene benzobisoxazole) fiber, carbon fiber, and polyimide fiber.

7. The multiphase polyolefin composite particle asphalt modifier according to claim 1, characterized in that: The crosslinking agent is prepared by mixing ethylene-octene copolymer and functional aminosiloxane in a weight ratio of (2-3):(1.5-3.5), and the functional aminosiloxane is one of 3-aminopropyl dimethoxymethylsilane and self-ureapropyl triethoxysilane.

8. The multiphase polyolefin composite particle asphalt modifier according to claim 1, characterized in that: The auxiliary agent is formed by mixing an oxidant, a softener and a promoter in a weight ratio of (1-2):(2-3):(0.5-1); the antioxidant is one or two of 2,6-di-tert-butyl-p-cresol and 1,1,3-tri(2-methyl-4-hydroxy-5-tert-butylphenyl)butane in any proportion; the softener is one or two of dioctyl terephthalate, dioctyl phthalate and dibutyl phthalate in any proportion; the promoter is one or two of promoter ZDC and promoter CZ in any proportion.

9. The multiphase polyolefin composite particle asphalt modifier according to claim 1, characterized in that: The waste tire rubber is 40-100 mesh waste tire rubber particles.

10. The method for preparing the heterogeneous polyolefin composite particle asphalt modifier according to claim 1, characterized in that: Add recycled EVA plastic particles, waste tire rubber powder particles, cross-linking agent and additives into a twin-screw extruder, mix for 10-20 minutes at a temperature of 50-70°C and a rotation speed of 100-200rpm, add recycled ABS plastic particles and high-strength fiber capsules in proportion after mixing evenly, continue mixing for 15-25 minutes at a temperature of 50-70°C and a rotation speed of 100-200rpm, and then extrude and granulate to obtain a multiphase polyolefin composite particle asphalt modifier.